RANCANG BANGUN GENERATOR AKSIAL DENGAN MENGGUNAKAN MAGNET PERMANEN NdFeB PERSEGI PANJANG - Sudirman Syam (Universitas Nusa Cendana, 2021)
Axial generators or Permanent Magnet Axial Flux (AFPM) are low-speed generators commonly used in Wind Power Plants (WPP). This generator has the rotor and stator position perpendicular to its axis. The rotor has permanent magnets, and the stator has copper wire coils. The purpose of this study was to analyse the output voltage characteristics of an axial generator using a permanent magnet of the Neodymium Ferrite Boron (NdFeB) type was arranged in layers. The method used is to design, manufacture, and measure the output of an axial generator with no load and load. Based on the research results, a no-load generator with a four-layer magnetic rotor produces the highest output voltage of 3.06 – 10.77 Volts at a rotor rotation speed of 360 rpm – 1328 rpm. Meanwhile, under conditions of 5 W DC lamp, the rotational speed of the rotor decreases between 355 – 1335 rpm, the output voltage is between 2.85 –5.86 Volts.